EVALUASI STRATEGI PEMERINTAH KOTA PEKANBARU DALAM MEMPERTAHANKAN ADIPURA TAHUN 2014-2015 - Septiana, Indah; Rusli. SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Adipura program is an environment department strategy program to create a neat and shade city. Pekanbaru was one of big city in Indonesia that gained 10 adipura award since 2004 till 2014. Although Pekanbaru gained adipura award many times, the reality is Pekanbaru was not proved as a clean of trash city. There are many trashes that scattered around side of the road and there are many stacks of trash in the dumpster. This research aims to evaluate Pekanbaru government strategies on defending adipura in 2014 – 2015.Base on data obtained from cleanliness and landscaping department, Pekanbaru has five strategies on defending adipura award which is do the cooperation and coordination to improve the technology and capacity of trash management facilities, utilization of human resources, build institution and technology to support the basic tasks and functions of public service, optimizing the usage of whole of department facilities, utilization of Pekanbaru government’s commitment through the maintenance and addition of facilities and infrastructures needed, suppress and reduce the volume of trash in the household which is expected can reduce the volume of trash transported. This research use qualitative descriptive method, data collection through observation and interviews the people who involved in this research as informants.The result of this research indicate that the evaluation of Pekanbaru government strategies on defending adipura 2014 – 2015 has not done well because just two of five strategies are implemented. This condition occurred because there was some problems which is the coordination by Pekanbaru cleanliness and landscaping department with PT. MIG was not maximal yet. There are many stack of trash and not transported entirely, then inadequate trash management’s facilities and infrastructures, socialization was not held thoroughly to public. The factors that effect the evaluation strategy of Pekanbaru government are the facilities and infrastructures, the public awareness and the fund.Keywords : Evaluation, Strategy, Adipura award of Pekanbaru